Phylloplane microflora for the control of bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae - H.D. CHOWDHURY2, P. SAIKIA1 and (Indian Phytopathology, 2002)
Different cell concentrations of phylloplane microflora were evaluated for the control of bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo). All the microorganisms including the heat killed and avirulent cells of the pathogen showed antagonistic effect towards Xoo and the control was better with their higher levels. However. Erwinia herbicola controlled the pathogen most effectively even at lowest ratio (1:1) and registered more than 90 per cent reduction in disease development at 50:1. Bacillus subtilis also performed better than other antagonists in reducing the build up of the bacterial leaf blight of rice. Tip clipping method of inoculation exhibited significantly more protection than swab and infiltration methods. The antagonistic/protective effect of the phylloplane microflora while inoculated in combination got reduced against Xoo.